Low-dose combined oral contraceptive use is associated with lower bone mineral content variation in adolescents over a 1-year period - Biason, Talita Poli [UNESP]; Goldberg, Tamara Beres Lederer [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Moretto, Maria Regina [UNESP]; Teixeira, Altamir Santos [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP] (Biomed Central Ltd, 2015)
Background: Low-dose combined oral contraceptives (COCs) can interfere with bone mass acquisition during adolescence. This study aimed to evaluate bone mineral density (BMD) and bone mineral content (BMC) in female adolescents taking a standard low-dose COC (ethinylestradiol 20 mu g/desogestrel 150 mu g)over a 1-year period and to compare their data with those of healthy adolescents from the same age group not taking COCs.Methods: This was a non-randomized parallel-control study with a 1-year follow-up. Sixty-seven adolescents aged from 12 to 19 years, divided into COC users (n = 41) taking 20 mu g ethinylestradiol/150 mu g desogestrel and COC non-user controls (n = 26), were evaluated by bone densitometry examinations at baseline and after 12 months. Comparisons between the groups at the study onset were performed using the Mann-Whitney test with the significance level fixed at 5% or p < 0.05. Comparisons between the groups at the study onset and after 12 months were based on variations in the median percentages for bone mass variables.Results: The COC users presented with low bone mass acquisition in the lumbar spine, and had BMD and BMC median variations of 2.07% and +1.57%, respectively, between the measurements at baseline and 12 months. The control group had median variations of +12.16% and +16.84% for BMD and BMC, respectively, over the same period. The total body BMD and BMC showed similar evolutions during the study in both groups. Statistical significance (p < 0.05) was seen for the BMC percentage variation between COC users and non-users.Conclusions: Use of a low-dose COC (ethinylestradiol 20 mu g/desogestrel 150 mu g) was associated with lower bone mass acquisition in adolescents during the study period.
Keywords: Adolescent; Bone density; Bone mineral content; Contraceptives; Osteoporosis